Determinants of caregiver burden in early onset dementia: Psychosocial factors and environmental design / Social networks. (7th December 2020) - Chiari, Annalisa; Pistoresi, Barbara; Galli, Chiara; Tondelli, Manuela; Vinceti, Giulia; Addabbo, Tindara; Zamboni, Giovanna
Abstract: Background: Caregivers of patients with early onset dementia (EOD) experience high levels of burden, which is known to be affected by financial and social variables, as well as by psychological features of the caregiver and patient's symptoms. However, it is not known how all these factors reciprocally interact in determining the burden of caregivers of EOD patients. We investigated multiple determinants of burden in a comprehensive model. Method: Consecutive eligible patients with EOD and their caregivers were recruited from the Cognitive Neurology Clinic of the Modena University Hospital, Italy. Patients underwent extended clinical, imaging and neuropsychological assessment. Caregivers were interviewed and asked to fill in questionnaires to gain information on patients' symptoms, caregiver burden (Zarit Burden Interview), caregiver psychological distress (Relative Stress Scale). Patient/caregiver demographics, social and clinical variables were entered in linear multiple regression models and mediation models to explore if the effect on burden is mediated by stress. Result: Data from 89 EOD patient‐caregiver dyads were examined. Caregiver burden was positively related to female caregiver sex (b=0.44, p=0.0002), severity of patient's behavioral symptoms (b=0.32, p=0.0004), diagnostic delay (b=0.18, p=0.017) and financial distress of the family (b=0.28, p=0.0008). Significant factors reducing the burden were caregiver perception of patient's quality of life (b=‐0.20, p=0.005), disease duration (b=‐0.27, p=0.0003), caregiver age (b=‐0.31, p=0.0017), offspring number (b=‐0.25, p=0.0004), patient's education (b=‐0.15, p=0.022), region of birth (b=‐0.17, p=0.025) and number of days off work (b=‐0.15, p<0.0001) (adjusted‐R 2 =0.64). While the effect of financial distress, number of caregiver's days off‐work, patient's disease duration, and caregiver sex was entirely mediated by the level of caregiver stress, the effect of diagnostic delay and of proxies of family or social network on burden was direct. Conclusion: Most of the effect of the known determinants of the burden of caregivers is mediated by caregivers' level of stress, in particular for female caregivers. In particular, the number of days off‐work that the caregiver can take is a variable on which action can be taken to reduce the caregivers' stress, hence their burden. However, as some determinants are independent from stress, direct actions should be aimed at increasing social networks and shortening diagnostic delay to reduce caregiver burden.